Reproductive Ethics New Challenges and Conversations - Campo-Engelstein, Lisa.; Burcher, Paul.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book summarizes the contributions at an April 2016 conference held at Albany Medical College, Reproductive Ethics: New Challenges and Conversations. Reproductive ethics does not suffer from a lack of challenging issues, yet a few "hot button" issues such as abortion and surrogacy seem to attract most of the attention, while other issues and dilemmas remain relatively underdeveloped in bioethics literature. The goal of this book is to explore and expand the range of topics addressed in reproductive ethics. This is a multi-disciplinary book bringing together philosophers, clinicians, sociologists, anthropologists, and other scholars whose research or clinical interests touch reproductive issues. The results of this compilation are a comprehensive and unique discussion of the evolving issues in the rapidly changing field. The majority of the popular reproductive ethics anthologies were published at least 10 years ago. The field of reproductive ethics would benefit from a new anthology that addresses some of the perennial dilemmas in reproductive ethics (e.g. abortion, sex selection) from updated perspectives and that also covers new technologies that have emerged only in the last few years, such as social egg freezing. .
Introduction by Lisa Campo-Engelstein and Paul Burcher -- Part 1: Genetic Testing and Enhancement -- 2.Zooming out: Solidarity in the Moral Imagination of Genetic Counseling by Jazmine Gabriel -- 3.Enhancing Future Children: How It Might Happen, Whether It Should by Susan B. Levin -- 4.The Decision to Know: Pregnancy and Epistemic Harm by Kirsten M. Kringle-Baer -- Part2: Fertility Preservation -- 5.Egg Freezing and the Feminist Quest for Equality in the Workplace by Karey Harwood -- 6.Fertility Preservation in Transgender and Gender Nonconforming Youth and Adolescents by Steph deNormand -- Part 3:Childbirth -- 7.Rights and Realities in US Maternity Care by Hermine Hayes-Klein -- 8.The Periviable Cesarean Section: Can a Case Be Made for Expanding Beneficence in Decision-Making? by Tara A. Lynch and Paul Burcher -- Part 3:Abortion, Surrogacy and Circumcision -- 9.(3z(BTeaching Morality by Teaching Science:(3y (BReligiosity and Abortion Regret by Alesha Doan and J. Shoshanna Ehrlich -- 10.My Child, Your Womb, Our Contract: The Failure of Contract Law to Protect Parties in Gestational Surrogacy by Claire Horner -- 11.Vulvar Nick and Metzitzah B$1 (BPeh: Punishment or Harm Reduction? by Allan J. Jacobs and Kavita Shah Arora.s
Keywords: Medicine; Laboratory medicine; Bioethics; Reproductive medicine; Medical ethics; Medicine & Public Health; Reproductive medicine; Theory of Medicine/Bioethics.; Bioethics; Laboratory medicine